Modified microacoustomechanical noise-immune gyroscope - Igor P. Miroshnichenko; Valery P. Sizov (Advanced Engineering Research)
The work objective is to develop a new modified microacoustomechanical noise-immune gyroscope. It allows converting the angular rotation velocities of the support base into electrical signals on two axes of rotation simultaneously. In addition, the valid signal level is increased compared to the noise interference level. This explains the expandability of the new modified microacoustomechanical gyroscope compared to the existing analogues. The operating principle of the modified gyro is specified in detail. The concept of its design and performance is explained in drawings. The proposed technical solution is protected by the Russian Federation patent for the invention. The proposed gyroscope can be used in the navigation, positioning and control systems of various mobile objects in aviation, rocket and space technology, robotics, etc.